2012
DOI: 10.1002/lsm.22078
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of laser stimulation by near infrared pulses of retinal and vestibular primary neurons

Abstract: These results show that infrared laser radiations provide a possible way to safely stimulate retinal and vestibular ganglion neurons. A similar temperature threshold is required to trigger neurons independently of variable energy thresholds, suggesting that an absolute temperature is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches also offer the long-term prospect of remotely affecting aberrant localized neural circuits that underlie many neurological diseases. A multitude of INS-related studies explored the ability of short-wave infrared (IR) pulses to stimulate neural structures including peripheral [3,4] and cranial nerves [5][6][7][8][9][10], retinal and cortical neurons [10][11][12], as well as cardiomyocytes [13,14]. It is stipulated that the INS phenomenon is mediated by temperature transients induced by IR absorption [15][16][17]; such transients can alternatively be induced using other forms of photoabsorption [18][19][20], or potentially by any other physical form of thermal neurostimulation that can be driven rapidly enough [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A depolarization was observed for the majority of DRG neurons even beyond the action potential energy threshold. Our previous works have shown that action potentials on retinal and vestibular neurons were obtained by the activation of the TRPV4 channels and with a constant temperature rise [15,16]. Our goal in this study was to check whether the same mechanism was involved to fire action potentials or to depolarize the neuron membrane without action potentials on DRG neurons.…”
Section: Introductionmentioning
confidence: 95%
“…Infrared laser pulses have been shown to induce intracellular calcium transients implicating mitochondria in neonatal cardiomyocytes [10] and in neonatal spiral and vestibular ganglion neurons [11] and to depolarize membranes in HEK293 cells [12], dorsal root ganglion neurons [13], oocytes, HEK cells and artificial layers [14], retinal and vestibular primary neurons [15,16], hippocampal neurons [17], spiral ganglion neurons [18], brain slices [19] and in vestibular hair cells and afferent neurons [20]. What remains unclear is whether an universal photothermal mechanism exists and how the transient heating induced by the IR laser pulse elicits membrane depolarization of neurons and action potentials or modulates intracellular signalling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation